2012
DOI: 10.3852/11-427
|View full text |Cite
|
Sign up to set email alerts
|

Description and life cycle of a new Physarum (Myxomycetes) from the Atacama Desert in Chile

Abstract: A new species of Physarum (Myxomycetes), Physarum atacamense is described in this paper, and details are provided on its life cycle as observed in spore-to-spore culture in agar. The new species was collected during studies of the Atacama Desert in Chile. It has been collected directly in the field and isolated in moist chamber cultures prepared with material from an endemic cactus. The combination of characters that make this species unique in the genus are its large fusiform nodes of the capillitium, its lon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 8 publications
0
13
0
Order By: Relevance
“…2007), vegetative cellular and/or nuclear fusion (Seravin and Goodkov 1987; Michel and Smirnov 1999; Tekle et al. 2014), a distinct sexual morphotype (Schuster 1976) and putative amoeboid or flagellate gametes (Wrigley de Basanta et al. 2012).…”
Section: Introductionmentioning
confidence: 99%
“…2007), vegetative cellular and/or nuclear fusion (Seravin and Goodkov 1987; Michel and Smirnov 1999; Tekle et al. 2014), a distinct sexual morphotype (Schuster 1976) and putative amoeboid or flagellate gametes (Wrigley de Basanta et al. 2012).…”
Section: Introductionmentioning
confidence: 99%
“…It now appears that their presence in arid and semi-arid environments is more widespread than previously imagined, to a large degree due to the funding of the study of the warm drylands of America such as the Atacama Desert , the Monte Desert and Tehucán-Cuicatlán Valley in Mexico ). Many new species have been described (Lado & al., 1999Estrada-Torres & al., 2001Mosquera & al., 2003;, 2010a, 2012, highlighting the importance of myxomycetes in these extreme arid environments, in spite of their dependence on water to complete their life cycle.…”
Section: Introductionmentioning
confidence: 99%
“…; Wrigley de Basanta et al. , , , ). Phylogenetic relationships confirmed that Columellidia is composed of the paraphyletic Stemonitales and the monophyletic Physarales, with Echinosteliales as a sister group of both (Fiore‐Donno et al.…”
Section: Discussionmentioning
confidence: 97%
“…; Wrigley de Basanta et al. , , , ). In most of previous studies, plasmodia were fed with living bacteria or yeast which induced serious difficulty in culturing and purification.…”
mentioning
confidence: 97%